Ethnography and medicine: the utility of positivist methods in research. Issue 3 (3rd July 2022) - Hayre, C. M.; Blackman, S.; Hackett, P. M. W.; Muller, D.; Sim, J.
Abstract: This commentary discusses the methodological utility of ethnography within the medical space. Whilst a general consensus affirms that ethnography aligns with qualitative approaches, as identified within the existing medical literature, here, we demonstrate how quantitative [positivist] methods can also be incorporated. This paper begins by contextualising ethnographic approaches within medical contexts by demonstrating its empirical value within the existing literature. Next, we discuss the interconnection between the practice of 'doctoring' and ethnographic research, whereby doctors themselves use forms of inductive and deductive reasoning to treat and manage patients in their everyday context. This philosophical discussion not only links to the everyday practice of medical practitioners, but also critically reflects on the role of the first author, as a diagnostic radiographer. Lastly, this paper identifies the virtues of ethnographic research for medical students and/or medical doctors whereby the combination of qualitative and quantitative methods (within an ethnographic methodology) can lead to new empirical and methodological insights, enabling the creation of alternate research strategies and evidence. This methodological strategy may be best considered amongst medical students and/or early career medical researchers, but we also anticipate it to resonate and open further discussion with experienced medical practitioners and researchers transnationally.